Their Peace or Prosperity - Rainey, Brian (Journal of ancient Judaism, 2015)
This article contends that hereditary punishment, defined as, biblical scenarios in which an act committed by a person or a group of people has negative effects on the descendants of that person or people is the most prominent rationale offered for the exclusion of foreigners, or people(s) of the land(s) in Ezra 9-10 and Nehemiah 13. Whereas some exegetes contend that Ezra-Nehemiah excludes these foreigners due to a fear that idolatrous religious practices will proliferate among the Exile community, this article looks at how the appeals to Leviticus 18 and 20 in Ezra 9 and to Deuteronomy 23 in Nehemiah 13 reveal that these foreigners have been excluded because they committed offenses against Yahweh or the Exile community for which they and their descendants should be punished. Ezra 9, by referencing concepts found in Leviticus 18 and 20, claims that the local non-Judean population should be excluded because they committed abominations and thereby defiled the land. Nehemiah 13:1-3, by referencing Deut 23:4-9, claims that these foreigners should be excluded because they acted like Ammon and Moab by obstructing the Exile community's restoration. As a result, it is unclear whether or not Ezra-Nehemiah excludes all foreigners from the Exile community or whether the exclusion is limited to non-Judeans in close proximity, who were perceived to have committed an offense of some kind.